Anesthesiology — Reanimatology: Historical Aspects - V. V. Moroz; V. Yu. Vasilyev; A. N. Kuzovlev (Общая реаниматология)
The Editorial Board of the journal «Obshchaya Reanimatologiya» intends to publish a series of papers dedicated to the history of the science «Anesthesiology and Reanimatology». In the first paper, the authors attempted to gather historical facts concerning the development of anesthesia. This makes it possible to analyze the course of development of the thought of scientists and physicians, the time of striking discoveries in our specialty, to reflect the most important points that impulses the expansion and optimization of methods of anesthesia and resuscitation. The authors understand clearly that they have no sufficient number of factors associated with the history of anesthesiology and reanimatology and they will be grateful in receiving any comments and additional information on historical aspects, specialized sections of the science, bibliographic data of Russian and foreign sciences dealing with this specialty. The to offer apologies for possible inaccuracies since controversial questions occasionally arise as to authorship and priority of ideas and usage of any methods in practice. There are not sometimes coincidences in the dates of the same events in different references used by us. The authors believe that the proposed historical analysis will generally provide a keen insight into the overall picture of development of world anesthesiology and reanimatology.